Perancangan Alat Peniris Di Stasiun Penggorengan Dan Topping Industri Intip - Hidayatulloh, Muh Mukhlis, Eko Setiawan, ST., MT., Ph.D (2016)
The food industry in the city of Surakarta is growing along with the made his city of Surakarta city tours. Especially in fried rice crackers in the industrial city of Surakarta is run by small and medium businesses or SMBS, SMEs in this mode all the process of making rice crackers do, but in making rice crackers still the abundance of work done manually so that many employees who complained of pain on parts of her body.The purpose of this research is to know the parts of the body that hurt, then designing a tool that ergonomics and simultaneously can reduce oil drops can cause the risk of an accident. Research is beneficial to know parts of the operator's body where pain, obtainment design and the ergonomic tool that can reduce the oil drops can cause the risk of an accident. The data are processed on this research was obtained from the dissemination of Questionnaires nordic body measurement and Anthropometry folder directly to operators in the frying pan and topping. From the results of the deployment folder to the body of the nordic Questionnaire 17 respondents, body parts are often perceived pain is back as many as 8 respondents while on the left shoulder, the fingers of the right hand, right calf and left calf that complains very sick as 6 respondents. From the results of the proposed ergonomic tool design using data, besides Anthropometry in the granting of fixed operators topping position it works from a position of squats into a stand. On the design of the proposed tool also comes with a chamfer that can accommodate and stream from the remaining oil pan to fit.